2010 IEEE International Geoscience and Remote Sensing Symposium 2010
DOI: 10.1109/igarss.2010.5650862
|View full text |Cite
|
Sign up to set email alerts
|

The Slope Imaging Multi-polarization Photon-counting Lidar: Development and performance results

Abstract: The Slope Imaging Multi-polarization Photoncounting Lidar is an airborne instrument developed to demonstrate laser altimetry measurement methods that will enable more efficient observations of topography and surface properties from space. The instrument was developed through the NASA Earth Science Technology Office Instrument Incubator Program with a focus on cryosphere remote sensing. The SIMPL transmitter is an 11 KHz, 1064 nm, plane-polarized micropulse laser transmitter that is frequency doubled to 532 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
(10 reference statements)
0
22
0
Order By: Relevance
“…These are much more sensitive to low intensity signals, requiring lower powered lasers and so making the instrument lighter and cheaper. NASA's SIMPL (Dabney et al, 2010) and ICESat II (Harding et al, 2011) instruments currently in development are examples and Moussavi, Abdalati, Scambos, and Neuenschwander (2014) demonstrated that they can measure forest height. However they require repeated measurements to measure energy, either from a fixed position (Hernandez-Marin, Wallace, & Gibson, 2007;Wallace et al, 2012) or by averaging over an area (Moussavi et al, 2014), which introduces statistical errors on top of the error from inversion methods.…”
Section: System Pulsementioning
confidence: 98%
“…These are much more sensitive to low intensity signals, requiring lower powered lasers and so making the instrument lighter and cheaper. NASA's SIMPL (Dabney et al, 2010) and ICESat II (Harding et al, 2011) instruments currently in development are examples and Moussavi, Abdalati, Scambos, and Neuenschwander (2014) demonstrated that they can measure forest height. However they require repeated measurements to measure energy, either from a fixed position (Hernandez-Marin, Wallace, & Gibson, 2007;Wallace et al, 2012) or by averaging over an area (Moussavi et al, 2014), which introduces statistical errors on top of the error from inversion methods.…”
Section: System Pulsementioning
confidence: 98%
“…SIMPL is a multi-beam laser altimeter developed through the NASA Earth Science Technology Office Instrument Incubator Program [7]. SIMPL is a pathfinder for more efficient, next-generation spaceflight laser altimeters including ICESat-2.…”
Section: Methodsmentioning
confidence: 99%
“…The recently developed and active airborne photon counting LiDAR system called SIMPL (Slope Imaging Multi-polarization Photon Counting Lidar) [26] is a dual channel system that measures at two wavelengths (532 nm and 1,064 nm) in parallel and perpendicular polarization channels, and is a time-correlated single photon counting system deployed in an airborne platform. In this paper, we also use a time-correlated photon counting LiDAR system to acquire measurements from a small sample conifer to illustrate our techniques.…”
Section: Forest Monitoring Using Lidar Datamentioning
confidence: 99%